Nitrogen-doped carbon derived from horse manure biomass as a catalyst for the oxygen reduction reaction - Gasidit Panomsuwan; Chadapat Hussakan; Napat Kaewtrakulchai; Ratchatee Techapiesancharoenkij; Ai Serizawa; Takahiro Ishizaki; Apiluck Eiad‐ua (RSC Advances, 2022)
a combination of two- and four-electron pathways. Although the ORR activity of HMNCs was still not satisfactory and comparable to that of a commercial Pt/carbon catalyst, it showed better long-term durability. The results obtained in this work provide the potential utilization of HM as a precursor for ORR catalysts and other related applications.
Keywords: Electrocatalysts for Energy Conversion; Supercapacitor Materials and Fabrication; Nanomaterials for catalytic reactions